Direct electrolysis of CO2 using an oxygen-ion conducting solid oxide electrolyzer based on La0.75Sr0.25Cr0.5Mn0.5O3-delta electrode - Xu, Shanshan; Li, Shisong; Yao, Weitang; Dong, Dehua; Xie, Kui (Elsevier SA, 2013)
Composite fuel electrode based on redox-reversible La0.75Sr0.25Cr0.5Mn0.5O3 -delta (LSCM) can be operated without a flow of reducing gas. We demonstrate the efficient electrolysis of CO2 using a symmetric solid oxide electrolyzer with a configuration of LSCMeSDC/YSZ/LSCMeSDC at 800 degrees Celcius. The temperature dependence of LSCM conductivity in air and the oxygen partial pressure dependence are investigated and correlated to electrode polarization in the symmetric cell. The LSCM electrode exhibits low electrode polarization in air at 800 degrees Celcius (0.325 Ohm cm2), and the electrode polarization can be further reduced to 0.25 Ohm cm2 when passing current to activate LSCM electrodes. In contrast, the electrode polarization of the symmetric cell in CO2 reached 5-10 Ohm cm2 under OCV and low current. However, it is decreased to 0.5 Ohm cm2 at large currents (e.g. 100-200 mA cm-2) for electrode activation. The results of AC impedancespectroscopy and I-V tests indicate two main processes: the electrochemical reduction of LSCM fuelelectrode at low voltages and the electrolysis of CO2 at high voltages. The current efficiency reaches 69%, 58% and 56% at 1.0, 1.5 and 2.0 V for the electrolysis of CO2 at 800 degrees Celcius, respectively.